x^2+ 9x + 18 = 0
(x+6)(x+3)
x= -6 or x = -3
{-2, -9}, {-1, -18},{-2, 9} are wrong. your initial choice was good so go along with the initial one
2007-04-27 20:40:34
·
answer #1
·
answered by Tubby 5
·
0⤊
0⤋
simplest thanks to remedy this issue is to element x^ 2 – 9x + 18 = 0 this gives: (x-6)(x-3) = 0 { which resources x^2 - 3x - 6x + 18} Use the most of 0 products: if ab = 0, both a, b, or both should be equivalent to 0. for that reason (x-6) = 0 , or (x-3) = 0 x = 6 or 3 *Plug both numbers (one on the time) examine.
2016-12-05 00:16:30
·
answer #2
·
answered by ? 4
·
0⤊
0⤋
x^2+ 9x + 18 = 0
Find factors of the constant (18)
Constant does not have a pronumeral.
In this case, 3 and 6 are the factors
(x+6)
(x+3)
(x+6)(x+3) = 0
because
x^2+3x+6x+18 = 0
x^2+9x+18 = 0
Now, go back,
(x+6)(x+3) = 0
x+6=0
or
x+3=0
Hence, x = -6 or x=-3
2007-04-27 19:21:14
·
answer #3
·
answered by Kuan T 2
·
0⤊
0⤋
factorise the equation ... you will get (x+3)(x+6)
therefore either x=-3 or x= - 6
when x = -3
y=0 and when x = - 6 , y = - 10
therefore, the answer = (-3, 0) , (-6, -10)
2007-04-27 21:13:12
·
answer #4
·
answered by Mehn 3
·
0⤊
0⤋
(x + 9) (x + 2)
2007-04-27 19:26:48
·
answer #5
·
answered by Zak S 3
·
0⤊
1⤋
x^2 +3x +6x +18=0
(x+3)(x+6)=0
x+3=0 ,,,,,,,,,x1= -3
x+6=0 ,,,,,,,, x2= -6
.
2007-04-27 19:25:19
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋
It's (x+6)(x+3)
x=-6 and x=-3
Your initial answer was right, who told you it was wrong?
..zak ur answer is very wrong
2007-04-27 19:29:57
·
answer #7
·
answered by surfing86 2
·
0⤊
0⤋
(x + 3).(x + 6) = 0
x = - 3, x = - 6 IS CORRECT
2007-04-27 21:01:25
·
answer #8
·
answered by Como 7
·
0⤊
0⤋